Systematic review and meta-analysis of prognostic factors of acute exacerbation of idiopathic pulmonary fibrosis - Kamiya, Hiroyuki (BMJ Open, 2020)
OBJECTIVE: To clarify prognostic factors of acute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF). DESIGN: A systematic review and meta-analysis. DATA SOURCES: Medline, Embase and Science Citation Index Expanded were searched from 2002 through 1 March 2019. ELIGIBILITY CRITERIA FOR SELECTING STUDIES: The review included primary studies addressing the association between the outcomes such as all-cause mortality of AE of IPF and its potential prognostic factors, which were designated as any clinical information related to the outcomes. DATA EXTRACTION AND SYNTHESIS: Two reviewers extracted relevant data independently and assessed risk of bias. Univariate results were pooled using a random-effect model if at least three studies were available. Prognostic factors were determined based on significant and consistent results on both univariate and multivariate analyses in the majority of studies. RESULTS: Out of a total of 6763 articles retrieved, 37 were eligible and 31 potential prognostic factors for all-cause mortality were selected. Each study was subject to certain methodological shortcomings. The following five factors were statistically significant by a meta-analysis of univariate results, which was confirmed by multivariate analysis, that is, Acute Physiology and Chronic Health Evaluation (APACHE) II score (HR 1.10, 1.01 to 1.19), partial pressure of arterial oxygen to fraction of inspired oxygen (PaO(2)/FiO(2)) ratio (ORs 0.99 in two studies and HRs 0.31 and 0.99 in two studies, respectively), lactate dehydrogenase (LDH) (HRs 1.002, 1.003, 1.01 and 1.02), white blood cell (WBC) count (OR 1.38, 1.04 to 1.83) and oxygen therapy before AE (HRs 3.68, 1.05 to 12.9 and 2.34, 1.04 to 5.28) (multivariate analysis, 95% CI). CONCLUSIONS: APACHE II score, PaO(2)/FiO(2) ratio, LDH, WBC count and oxygen therapy before AE were deemed as prognostic factors of AE of IPF. Although there are some methodological limitations in this study, these findings are reliable due to consistent results by both univariate and multivariate analyses. PROSPERO REGISTRATION NUMBER: CRD42018106172.